Return to Play After Arthroscopic Stabilization for Posterior Shoulder Instability-A Systematic Review - Jordan W. Fried, B.M; Eoghan T. Hurley, M.B., B.Ch., M.Ch; Matthew L. Duenes, B.S; Amit K. Manjunath, B.S; Mandeep Virk, M.D; Guillem Gonzalez-Lomas, M.D; Kirk A. Campbell, M.D (Elsevier, 2021)
Purpose: To ascertain the rate and timing of return to play (RTP) and the availability of specific criteria for safe RTP after arthroscopic posterior shoulder stabilization. Methods: Medline, EMBASE, and the Cochrane Library were searched according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines to find studies on arthroscopic posterior shoulder stabilization. Studies were included if they reported RTP data or rehabilitation protocols and excluded if concomitant procedures influenced the rehabilitation protocol. Rate and timing of RTP, along with rehabilitation protocols, were assessed. Results: This review found 25 studies, including 895 cases, meeting the study's inclusion criteria. The majority of patients were male (82.7%), with an age range of 14 to 66 years and a follow-up range of 4 to 148.8 months. The overall RTP rate ranged from 62.7% to 100.0%, and 50.0% to 100.0% returned to the same level of play. Among collision athletes, the overall rate of RTP was 80.0% to 100.0%, with 69.2%-100.0% returning to the same level of play. In overhead athletes, the overall rate of RTP was 85.2% to 100.0%, with 55.6% to 100.0% returning to the same level of play. Four studies (128 patients) specifically addressed the timing of RTP, and the range to RTP was 4.3 to 8.6 months. Specific RTP criteria were reported in a majority of studies (60%), with the most reported item being restoration of strength (44%). Conclusion: There is a high rate of return to sport after arthroscopic posterior shoulder stabilization, ranging from 4.3 to 8.6 months after surgery. Return to preinjury level is higher for collision athletes compared with overhead athletes. However, there is inadequate reporting of RTP criteria in the current literature, with no clear timeline for when it is safe to return to sport. Level of Evidence: IV, systematic review of level II to IV studies